Airport competition from airports' perspective: Evidence from a survey of European airports. Issue 3 (September 2020) - Bilotkach, Volodymyr; Bush, Harry
In this study, we describe the results of a questionnaire distributed among European airports in the autumn of 2019. The questionnaire was designed to elicit airports' views on the practicalities of competition between airports. We received 49 responses from airports in 24 countries; the respondents represent airports of different sizes. The survey results evidence behaviours consistent with significant competition between airports. Airports are taking active steps through their resourcing and staffing, incentives and marketing to attract airline services, and clearly see themselves taking the initiative in doing so. No airport, no matter how large, appears to be able to escape competition. The main policy message of our study, consistent with other recent reviews of airport competition, is that European regulators should re-evaluate their approach to the economic regulation of airports, especially as far as regional airports are concerned.